Analisa Perbandingan Hasil Trombosit Pada Alat Hematologi Analyzer Metode Impedance dan Metode Optik Pada Kasus Anemia Hipokrom Mikrositer (Berdasarkan Indeks Eritrosit) - Maulina Rosida; Budiono Raharjo; Halik Wijaya (Faculty of Health Sciences Universitas Maarif Hasyim Latif, 2023)
Platelets have an important role in hemostasis, namely the formation and stabilization of platelet plugs. There are several methods in the counting of platelets. They can be carried out in a direct and an indirect manner. The direct method can be carried out in an automatic and automatic way. The automatic method uses an hematology analyzer which functions to measure and examine blood cells in blood samples. Counting the number of platelets is done automatically by two methods, namely optical and impedance which have different principles. The optical method is based on cell size and morphology, while impedance is based on cell size only. Hypochrome is a condition where the Hb concentration is less than normal so that the central achromia widens (> 1/3 of the cell) and there is a decrease in the color of the erythrocytes, namely an increase in the diameter of the central pallor above normal so that it looks paler. Microcyte is a condition where the cell size is smaller than normal. The purpose of this study was to determine the difference in the number of platelets in the hematology analyzer using the impedance method and the optical method in the case of microcytic hypochromic anemia (based on erythrocyte index) with a descriptive analytical research design. The test used is the paired t-test with a total sample of 30 samples. The results of platelets using the impedance method have an average of 339.37 * 103 / uL with a standard deviation of 120.294. The results of platelets using the optical method have an average of 314.70 * 103 / uL with a standard deviation of 113.569. A significant value of 0.000 significant value of (sig. < 0.05) can be concluded that there is a difference between the results of platelets on the hematology analyzer using the impedance method and the optical method in cases of microcytic hypochromic anemia (based on erythrocyte index). Keywords : Trombosit, Hipokrom Mikrositer, Hematology analyzer, Impedance, Optik.